2018
DOI: 10.1128/mbio.01872-18
|View full text |Cite
|
Sign up to set email alerts
|

Using Lipoamidase as a Novel Probe To Interrogate the Importance of Lipoylation in Plasmodium falciparum

Abstract: Lipoate is an essential cofactor for a small number of enzymes that are important for central metabolism. Malaria parasites require lipoate scavenged from the human host for growth and survival; however, it is not known why this cofactor is so important. To address this question, we designed a probe of lipoate activity based on the bacterial enzyme lipoamidase (Lpa). Expression of this probe in different subcellular locations allowed us to define the mitochondrion as the compartment housing essential lipoate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In contrast to human and yeast cells, FASII enzymes in P. falciparum are absent from the mitochondrion and targeted instead to the apicoplast organelle (Table S1) (11). Although critical lipoate-dependent enzymes are present in the parasite mitochondrion (2), prior work has shown that these enzymes utilize scavenged lipoate obtained from the red blood cell rather than de novo synthesis (12).…”
Section: Significance Statementmentioning
confidence: 99%
“…In contrast to human and yeast cells, FASII enzymes in P. falciparum are absent from the mitochondrion and targeted instead to the apicoplast organelle (Table S1) (11). Although critical lipoate-dependent enzymes are present in the parasite mitochondrion (2), prior work has shown that these enzymes utilize scavenged lipoate obtained from the red blood cell rather than de novo synthesis (12).…”
Section: Significance Statementmentioning
confidence: 99%
“…In contrast to human and yeast cells, FASII enzymes in P. falciparum have been lost by the mitochondrion and are retained instead by the apicoplast organelle (Figure 1figure supplement 1) (12). Although critical lipoate-dependent enzymes are present in the parasite mitochondrion (2), prior work has shown that these enzymes utilize scavenged lipoate obtained from the red blood cell rather than de novo synthesis (13).…”
Section: Introductionmentioning
confidence: 96%
“…Understanding the unique biochemical pathways that specialize parasites for growth within human red blood cells will shed light on their evolutionary divergence from other eukaryotes and unveil new parasite-specific targets for development of novel antimalarial therapies. P. falciparum retains an essential mitochondrion required for biosynthesis of pyrimidines, acetyl-CoA, and Fe-S clusters (1)(2)(3)(4)(5). Although the parasite mitochondrion also contains enzymes involved in the citric acid cycle and biosynthesis of ATP and heme, these pathways are dispensable for blood-stage parasites, which can scavenge host heme and obtain sufficient ATP from cytoplasmic glycolysis (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…There is mounting evidence that lipoic acid metabolism is required for microbial pathogenesis (22). For example, in malariacausing Plasmodium species, lipoic acid synthesis and salvage are essential during liver-stage and asexual blood-stage development, respectively (22)(23)(24)(25)(26)(27). In Listeria monocytogenes, a lipoic acid auxotroph, salvage of the cofactor contributes to growth in the host cytosol and disease in mice (28)(29)(30).…”
mentioning
confidence: 99%